Spectacles and the Victorians : Measuring, defining and shaping visual capacity. - ALMOND-BROWN, GEMMA (Book collections on Project MUSE., 2023)
This book explores how the Victorians standardised vision and transformed spectacle use. It offers new insights into how technology and its adoption in medical and non-medical contexts shaped, and continues to shape, our understanding of sensory perception and the assimilation of assistive devices.